2016
DOI: 10.1002/2016jd025209
|View full text |Cite
|
Sign up to set email alerts
|

Data-model comparison of temporal variability in long-term time series of large-scale soil moisture

Abstract: Soil moisture is at the heart of many processes connected to water cycle, climate, ecosystem, and societal conditions. This paper investigates the ability of a relatively simple analytical soil moisture model to reproduce temporal variability dynamics in long‐term data series for (i) remotely sensed large‐scale water storage change in 25 large catchments around the world and (ii) measured soil water content and groundwater level in individual stations within 10 smaller catchments across the United States. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Because this additional dampening effect is accounted for in ( σ R / σ P ), so is also the influence of lakes and wetlands on trueP¯ partitioning (van der Velde, Lyon, & Destouni, ) and through that on ( σ R / σ P ). The trueP¯ partitioning, and through that the dampening factor ( σ R / σ P ), may also be further affected by hydrological seasonality (Verrot & Destouni, ), long‐term changes in climate (van der Velde et al, ), and human land and water uses (Destouni, Jaramillo, & Prieto, ; Jaramillo & Destouni, ). In this study, we want to capture all possible influences on flow‐variability dampening due to lakes and wetlands and use therefore the standard deviation relation ( σ R / σ P ) as our primary comparative flow dampening factor.…”
Section: General Conceptual and Quantification Basismentioning
confidence: 99%
“…Because this additional dampening effect is accounted for in ( σ R / σ P ), so is also the influence of lakes and wetlands on trueP¯ partitioning (van der Velde, Lyon, & Destouni, ) and through that on ( σ R / σ P ). The trueP¯ partitioning, and through that the dampening factor ( σ R / σ P ), may also be further affected by hydrological seasonality (Verrot & Destouni, ), long‐term changes in climate (van der Velde et al, ), and human land and water uses (Destouni, Jaramillo, & Prieto, ; Jaramillo & Destouni, ). In this study, we want to capture all possible influences on flow‐variability dampening due to lakes and wetlands and use therefore the standard deviation relation ( σ R / σ P ) as our primary comparative flow dampening factor.…”
Section: General Conceptual and Quantification Basismentioning
confidence: 99%
“…However, these effects are complex (Reichstein et al, 2013;Knapp et al, 2015;Bartlett et al, 2016), with the drought response of plants (partly) non-linearly depending on various factors. These comprise vegetation characteristics, such as root depth, leaf area, and plant physiology; soil characteristics, such as water holding capacity; and hydrological and terrain characteristics, which in turn affect groundwater level and thereby also soil moisture conditions above (Destouni and Verrot, 2014;Verrot and Destouni, 2016). Moreover, drought history can also play a role through legacy effects (Seneviratne et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate characterization of RZSM in land surface models, terrestrial biosphere models, and earth system models is critical for accurately estimating short‐term (hourly‐yearly), medium‐term (yearly‐to‐decadal), and long‐term (decadal‐to‐centennial) carbon, water, and energy fluxes. With regard to water fluxes, previous studies have shown that there are model‐dependent, systematic biases in model‐based estimates of soil moisture or RZSM when against ground observations (Koster et al, ; Loew et al, ; Pan et al, ; Verrot & Destouni, ; Xia et al, ) and remotely sensed measurements of near‐surface soil moisture (Gumuzzio et al, ; Polcher et al, ), and that models show divergent biases (van den Hurk et al, ). With respect to carbon fluxes, Kim et al () demonstrated the importance of soil moisture stress response functions for predictions of carbon fluxes in the Ent Terrestrial Biosphere Model.…”
Section: Introductionmentioning
confidence: 99%